Evaluation on development efficiency of low-carbon tourism economy: A case study of Hubei Province, China - Zha, Jianping; He, Lamei; Liu, Yang; Shao, Yuhong (Socio-economic planning sciences, 2019)
Tourism is one of the emissions sources of CO2 and tourism activities can impose pressure on the ecological environment. The study constructed an evaluation framework of the direct and indirect CO2 emissions from tourism industry, and included the CO2 emission factor in the efficiency evaluation framework based on SBM-Undesirable model, on the basis of which, the study assessed the CO2 emissions from the tourism industry, taking the cities of Hubei province in China as case studies, and then measured and analyzed the development efficiency of low-carbon tourism economy in the cities and its dynamic fluctuations in the cities from 2007 to 2013. The results show that the total carbon dioxide emissions from tourism in Hubei soared from 6,340,302 tons in year 2007 to 23,939,851 tons in year 2013, with the transportation being the biggest contributor accounting for 50.35% of the total emissions, followed by the food, accommodation, shopping, other services, entertainment, post & telecommunications. While the direct CO2 emission far exceeds that of the indirect in the transportation, the opposite is true in other secondary sectors. Results of efficiency measurement indicate the overall efficiency of low-carbon tourism economy is on a rather low level and varies significantly among the cities, and there are untapped potentials with internal productive factors in the economic system of urban tourism. From the perspective of dynamic shifts, however, the overall efficiency within the analyzed period was on an upward trend, driven primarily by the technological advancements induced by the scale factor, whereas the purely technological efficiency changes undermined the growth of productivity. Finally, the calculation results of slack variables in inputs and outputs based on the efficiency evaluation framework achieved in this study will provide reference for development efficiency modification of low-carbon tourism economy in inefficient cities. •CO2 emissions from the tourism industry of 17 cities of Hubei Province in China from 2011 through 2013 were calculated.•Based on SBM-Undesirable model, an evaluation framework was constructed and applied in low-carbon tourism context.•Guidance for the ineffective cities to achieve potential improvements was proposed.